A systematic review of the adverse events and economic impact associated with oral corticosteroids in asthma. (2nd December 2019) - Al Efraij, Khalid; Johnson, Kate M.; Wiebe, Darrin; Sadatsafavi, Mohsen; FitzGerald, J. Mark
Abstract: Background: Oral corticosteroids (OCSs) are often used to achieve asthma control. OCS-related comorbidities increase the burden of disease for patients and healthcare providers. Most studies characterizing OCS use and risk of adverse events (AEs) are in non-asthma patients. We sought to systematically review the literature on the burden of OCS use among adults with asthma. Methods: We systematically reviewed the literature including MEDLINE (1946–May 2017), EMBASE (1974–May 2017), and the Cochrane Library (2005–May 2017) to identify studies that considered AEs due to OCS treatment of adults with asthma, their burden on healthcare utilization, and costs. Results: We retrieved 9, 589 citations; and 15 studies were included. AEs were significantly higher among OCS-users compared with non-OCS users with pooled adjusted odds ratio (OR) 1.68 (95% CI 1.15–2.46) for diabetes mellitus and 1.34 (95% CI 1.23–1.46) for hypertension. Among high dose OCS-users (>10 mg) compared with non-OCS users, the pooled adjusted ORs for development of any complication was 3.35 (95% CI 2.94–3.82), and bone and muscle complications 2.30 (95% CI 2.18–2.42). The risk of any complication increased with higher doses of OCS, with pooled adjusted OR from 2 studies of 2.26 (95% CI 1.37–3.72), 2.94 (95% CI 2.62–3.29) and 3.35 (95% CI 2.94–3.82) for low dose (<6 mg), medium dose (5–12 mg) and high dose (>10 mg) respectively compared with no OCS use. Conclusions: The use of OCS in the management of asthma is associated with a higher risk of complications. This risk is higher as the OCS dose increases.